Growth and Yield of Melon with the Application of Liquid Organic Fertilizers at Different Peat Maturity Levels: Pertumbuhan dan Hasil Melon dengan Pemberian Pupuk Organik Cair pada Berbagai Tingkat Kematangan Gambut - Radian; Tatang Abdurrahman; Mahmudi (Agrifarm : Jurnal Ilmu Pertanian, 2025)
This study aimed to evaluate the effects of liquid organic fertilizers on the growth and yield of melon plants cultivated on peat soils with different decomposition levels. The experiment was conducted from April to November 2024 at the experimental field on Jalan Reformasi, Pontianak, West Kalimantan, using a factorial Completely Randomized Design with two factors and three replications. The first factor was the type of liquid organic fertilizer (cow urine, Jadam, Jakaba, and NASA), and the second factor was peat maturity level (fibric, hemic, and sapric). The results indicated no significant interaction between liquid organic fertilizers and peat maturity levels on plant height, leaf number, fruit diameter, fruit circumference, or fruit weight per plant. Peat maturity levels had similar effects across all growth and yield parameters. Among the fertilizers, NASA liquid organic fertilizer and cow urine produced the highest fruit diameter, fruit circumference, and fruit weight per plant.